A history of communications : media and society from the evolution of speech to the Internet - Poe, Marshall (Cambridge ; New York : Cambridge University Press, 2011)
"Communications and Humanity advances a new theory of media that explains the origins and impact of different forms of communication - speech, writing, print, electronic devices, and the Internet - on human history in the long term. New media are "pulled" into widespread use by broad historical trends and these media, once in widespread use, "push" social institutions and beliefs in predictable directions. This view allows us to see for the first time what is truly new about the Internet, what is not, and where it is taking us"--Provided by publisher.
Introduction : media causes and effects -- Homo loquens : Humanity in the age of speech -- Homo scriptor : humanity in the age of manuscripts -- Homo lector : humanity in the age of print -- Homo videns : humanity in the age of the audiovisual media -- Homo somnians : humanity in the age of Internet -- Conclusion : the media and human well-being.
Includes bibliographical references and index.
Keywords: Communication -- Social aspects; Digital media -- Social aspects